A Sphere-Based Calibration Method for Line Structured Light Vision Sensor. (20th November 2013) - Wei, Zhenzhong; Shao, Mingwei; Wang, Yali; Hu, Mengjie
Abstract : A major difficulty in calibrating line structured light vision sensor is how to obtain enough calibration feature points, due to the fact that known world points on the calibration target do not rightly fall onto the light stripe plane. This paper presents a calibration method using a target, consisting of one sphere and a reference board, to obtain feature points on the light stripe, which is the intersection of the structured-light plane and the reference board. By moving the sphere into several positions on the fixed reference board, we can get a plane in parallel with the reference one. From the acquired right-circular cone and known radius of the sphere, the function of the reference board can be deduced. Moving the target randomly into different positions, enough points lying on the structured-light plane can be obtained. Experiment results show that the accuracy of the proposed calibration method can reach 0.102 mm within the view field of 200 mm * 200 mm; meanwhile, robustness and easy operation can be indicated.